Towards reforming the regulatory and policy environment of the microbus system in the Greater Cairo Metropolitan Area - Ramadan, Amr (AUC Knowledge Fountain, 2015)
Over the last 2 decades the shared taxi, or microbus, has become the most important mode of transportation in the Greater Cairo, one of the world’s most congested cities. In a city with a largely ineffective public transit system, microbuses have become the city’s lifeline, meeting the demand for low cost, fast and timely transport. Incredibly, their development and operation has been mostly unplanned, informal and illegal, causing many to question their place in future plans to revamp the city’s ailing transport system. This study will focus on a detailed stakeholder analysis of the two key players in the microbus transport mode, the government planners and the microbus operators, giving insight into economic, political and social dimensions of the mode in general. More specifically, the study will examine their preferences on potential policy and regulatory reforms inspired by successful international experience in dealing with para-transit, for specific priority routes where Bus Rapid Transit lines are planned to be implemented.